Mitotic Maturation Compensates for Premature Centrosome Splitting and PCM Loss in Human cep135 Knockout Cells - Zhenzhen Chu; Oliver J. Gruss (Cells, 2022)
Centrosomes represent main microtubule organizing centers (MTOCs) in animal cells. Their duplication in S-phase enables the establishment of two MTOCs in M-phase that define the poles of the spindle and ensure equal distribution of chromosomes and centrosomes to the two daughter cells. While key functions of many centrosomal proteins have been addressed in RNAi experiments and chronic knockdown, knockout experiments with complete loss of function in all cells enable quantitative analysis of cellular phenotypes at all cell-cycle stages. Here, we show that the centriolar satellite proteins SSX2IP and WDR8 and the centriolar protein CEP135 form a complex before centrosome assembly in vertebrate oocytes and further functionally interact in somatic cells with established centrosomes. We present stable knockouts of SSX2IP, WDR8, and CEP135 in human cells. While loss of SSX2IP and WDR8 are compensated for, cep135 knockout cells display compromised PCM recruitment, reduced MTOC function, and premature centrosome splitting with imbalanced PCMs. Defective cep135 knockout centrosomes, however, manage to establish balanced spindle poles, allowing unperturbed mitosis and regular cell proliferation. Our data show essential functions of CEP135 in interphase MTOCs and demonstrate that loss of individual functions of SSX2IP, WDR8, and CEP135 are fully compensated for in mitosis.